Pengaruh Solvabilitas dan Profitabilitas terhadap Harga Saham pada Perusahaan Sektor Makanan & Minuman - Arie Pratania Putri; Slyvia Valencia; Angeline Anastacia Tan; Angellya Kumala Dewi; Alistraja Dison Silalahi (Universitas Batanghari Jambi, 2023)
The purpose of this study was to examine the effect of ROA, NPM, DER and DAR on Stock Prices. This research applied the documentation method by searching for data and downloading reports finance of various companies in the food & beverage business sector on the IDX during the period of 2019 to 2021. This research used purposive sampling technique, where there were a total of 66 data on 22 companies multiplied by 3 years of observation. The conclusion shows that NPM had an impact partially related to stock prices, while ROA, DER and then DAR were found not partially related on stock prices. Furthermore, the results of the study also show the four variables was found to have a simultaneous effect on stock prices. Based on the R squared test, it could be seen that each independent variable collects a percentage of 24.5% in influencing the dependent variable and the remaining percentages are driven by other types of variables that are outside of the research within 75.5%.